Biaxial Orientation of Poly(ethylene 2, 5‐furandicarboxylate): An Explorative Study. Issue 3 (16th January 2018) - van Berkel, Jesper G.; Guigo, Nathanaël; Kolstad, Jeffrey J.; Sbirrazzuoli, Nicolas
Abstract: The biaxial orientation behavior of poly(ethylene 2, 5‐furandicarboxylate) (PEF) is studied in comparison to poly(ethylene terephthalate) (PET). PEF is a polyester that can be produced through similar steps as PET but using 100% biobased 2, 5‐furandicarboxylic acid instead of terephthalic acid. This work highlights the stress–strain behavior of PEF during biaxial orientation at various temperatures. Strain hardening and strain‐induced crystallization in the oriented PEF samples generally appeared at higher stretch ratios for PEF than for PET at comparable molecular weight, while somewhat lower degrees of crystallinity are reached in PEF. Shrinkage in oriented PEF is found to be on par with PET in the region of the glass transition. Higher modulus and improved barrier properties, compared to PET, are found in the oriented materials when sufficiently high stretch ratios are applied in biaxial orientation. Abstract : Biaxial stretching of poly(ethylene 2, 5‐furandicarboxylate) (PEF) and its influence on thermal, mechanical, and barrier properties is explored in comparison to poly(ethylene terephthalate). Characteristics of the stretching behavior are forces being off‐set by PEF's higher T g and strain hardening occurring at higher stretch ratios.